Faktor-faktor yang Berhubungan dengan Sikap Ibu Hamil Tentang Skrining Hipotiroid Kongenital (SHK) di Klinik Alfatih Medika 2 Tahun 2024 - Laurensia Kurnia Baso; Wiwin Widyastuti (Universitas Pahlawan Tuanku Tambusai, 2025)
Deficiency of thyroid hormones in infants and early life, can result in stunted growth and mental retardation. This screening program has been included in the government program, but the coverage rate of congenital hypothyroid screening in Indonesia is still low, which is less than 2% (IDAI, 2015).To find out what are the factors related to the attitude of pregnant women about Congenital Hypothyroidism Screening (SHK) at Alfatih Medika Clinic 2.The method used in this study is analysis with a Cross Sectional approach with a total population of 195 people and a sample of 66 respondents obtained by simple random sampling.Of the 45 respondents who had poor knowledge about SHK, 62.2% did not receive SHK and 37.8% accepted SHK. Meanwhile, of the 21 respondents who had good knowledge, 81.0% received SHK, and those who did not receive 19.0%. The results of the statistical test (Fisher Excat test) p/p value = 0.001 (p˂0.05). Of the 32 respondents who showed an attitude of not accepting 68.8%, and those who accepted 31.3%. Meanwhile, of the 34 respondents who accepted SHK, it was found that the majority accepted SHK, which was 70.6% and 29.4% did not receive it. with a p/p value = 0.003 (p˂0.05). Of the 29 respondents who did not support SHK, 72.4% did not accept doing SHK and 27.6% did not accept SHK. Meanwhile, of the 37 respondents who supported it, it was found that 70.3% accepted to do SHK and 29.7% did not receive. With p/p value = 0.001 (p˂0.05).Statistically there is a significant relationship between knowledge, attitude and support of the husband, there is a mother's attitude towards SHK.